PENERAPAN MEDIA MINIATUR SIKLUS AIR DAN AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI SIKLUS AIR (Penelitian Tindakan Kelas pada Siswa Kelas V SDN Pasanggrahan III, Kecamatan Sumedang Selatan, Kabupaten Sumedang Tahun Pelajaran 2018/2019) - Indiani, Rita; Sujana, Atep; Kurnia Kayadinata, Asep (Jurnal Pena Ilmiah, 2019)
Â His study aims to overcome the problems regarding the low learning outcomes of students in the water cycle material in class V of SDN Pasanggrahan III, Sumedang Selatan District, Sumedang Regency. This type of research is Classroom Action Research conducted in 3 cycles with each cycle consisting of the stages of planning, implementation, observation, and reflection. The subjects in this study were fifth grade students of Pasanggrahan III Elementary School, amounting to 29 students. The instrument of data collection uses observation sheets, interview guidelines, question sheets, and questionnaire sheets. With the percentage of student learning outcomes that were declared complete in the initial data 34.48%, in the first cycle it reached 58.62%, in the second cycle it increased to 68.97%, and in the third cycle increased and had reached the target of 86.21% . Thus it can be concluded that the use of learning media "Miniature Water and Audio Visual Cycle" can improve student learning outcomes in water cycle aterial in class V of SDN Pasanggrahan III.Keywords: Miniature Water and Audio Visual Cycle media, science learning outcomes, water cycle material.Â